Fibroblast-Specific Proteotranscriptomes Reveal Distinct Fibrotic Signatures of Human Sinoatrial Node in Nonfailing and Failing Hearts. Issue 2 (13th July 2021) - Kalyanasundaram, Anuradha; Li, Ning; Gardner, Miranda L.; Artiga, Esthela J.; Hansen, Brian J.; Webb, Amy; Freitas, Michael A.; Pietrzak, Maciej; Whitson, Bryan A.; Mokadam, Nahush A.; Janssen, Paul M.L.; Mohler, Peter J.; et al.
Abstract : Background: Up to 50% of the adult human sinoatrial node (SAN) is composed of dense connective tissue. Cardiac diseases including heart failure (HF) may increase fibrosis within the SAN pacemaker complex, leading to impaired automaticity and conduction of electric activity to the atria. Unlike the role of cardiac fibroblasts in pathologic fibrotic remodeling and tissue repair, nothing is known about fibroblasts that maintain the inherently fibrotic SAN environment. Methods: Intact SAN pacemaker complex was dissected from cardioplegically arrested explanted nonfailing hearts (non-HF; n=22; 48.7±3.1 years of age) and human failing hearts (n=16; 54.9±2.6 years of age). Connective tissue content was quantified from Masson trichrome–stained head-center and center-tail SAN sections. Expression of extracellular matrix proteins, including collagens 1 and 3A1, CILP1 (cartilage intermediate layer protein 1), and POSTN (periostin), and fibroblast and myofibroblast numbers were quantified by in situ and in vitro immunolabeling. Fibroblasts from the central intramural SAN pacemaker compartment (≈10×5×2 mm 3 ) and right atria were isolated, cultured, passaged once, and treated ± transforming growth factor β1 and subjected to comprehensive high-throughput next-generation sequencing of whole transcriptome, microRNA, and proteomic analyses. Results: Intranodal fibrotic content was significantly higher in SAN pacemaker complex from HF versus non-HF hearts (57.7±2.6% versus 44.0±1.2%; P <0.0001). Proliferating phosphorylated histone 3 + /vimentin + /CD31 – (cluster of differentiation 31) fibroblasts were higher in HF SAN. Vimentin + /α-smooth muscle actin + /CD31 – myofibroblasts along with increased interstitial POSTN expression were found only in HF SAN. RNA sequencing and proteomic analyses identified unique differences in mRNA, long noncoding RNA, microRNA, and proteomic profiles between non-HF and HF SAN and right atria fibroblasts and transforming growth factor β1–induced myofibroblasts. Specifically, proteins and signaling pathways associated with extracellular matrix flexibility, stiffness, focal adhesion, and metabolism were altered in HF SAN fibroblasts compared with non-HF SAN. Conclusions: This study revealed increased SAN-specific fibrosis with presence of myofibroblasts, CILP1, and POSTN-positive interstitial fibrosis only in HF versus non-HF human hearts. Comprehensive proteotranscriptomic profiles of SAN fibroblasts identified upregulation of genes and proteins promoting stiffer SAN extracellular matrix in HF hearts. Fibroblast-specific profiles generated by our proteotranscriptomic analyses of the human SAN provide a comprehensive framework for future studies to investigate the role of SAN-specific fibrosis in cardiac rhythm regulation and arrhythmias. Abstract : Supplemental Digital Content is available in the text.